Using Lean tools to reduce patient waiting time. Issue 3 (8th June 2018) - Lot, Luciana Teixeira; Sarantopoulos, Alice; Min, Li Li; Perales, Simone Reges; Boin, Ilka de Fatima Santana Ferreira; Ataide, Elaine Cristina de
Abstract : Purpose: This paper aims to address problems in patient flow and identify the reasons behind extensive wait time at a public liver transplant outpatient clinic in an education and research hospital through the use of Lean health-care theories. Design/methodology/approach: This paper opted for the application of Lean thinking and action research strategy. Data were collected through personal observations, interviews with users and team brainstorming. A value stream map was developed, improvement possibilities were identified and non-value-added activities were attempted to be eliminated. Findings: Significant problems were identified and improvements were implemented and measured. The major remedial measures were: change the scheduling pattern, create a flow chart and a Kanban visual guide for medical students. In addition, an institutional change in the medical appointment scheduling software collaborated in the reduction of time and in the patient's displacement. The waiting time was reduced by 4.5 h, and the per cent complete and accurate increased by 50 per cent. Practical implications: The flow was redesigned, and a culture of continuous improvement was introduced. Visiting the place where work was being done, leaders identified and created more value to the process without significant costs. The Gemba Walk was a powerful tool, interacting with people and processes in a Kaizen spirit. Originality/value: Public health services in developing countries are one of the most deprived social needs of good practice. It will be useful for those who need examples about how to apply Lean tools in health care.